Preparation method of sulfonated polyetheretherketone proton exchange membrane
The metal organic frame array is combined with the sulfonated polyether ether ketone proton exchange membrane by spin coating, which solves the problem of poor dimensional stability of the sulfonated polyether ether ketone proton exchange membrane and realizes efficient application in CO2 reduction and hydrogen energy conversion technology.
Patent Information
- Application Number
- CN202510021757.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-01
AI Technical Summary
The sulfonated polyether ether ketone proton exchange membrane has poor dimensional stability when water molecules increase, resulting in increased channel size, reduced performance, and may eventually decompose the loss of the function of preventing gas cross-penetration.
The metal organic frame array is combined with the sulfonated polyether ether ketone proton exchange membrane by spin coating method, and the water absorption of the sulfonated polyether ether ketone is restricted by the ordered pore structure of the metal organic frame array, thereby improving its dimensional stability.
While maintaining the proton conduction ability, the dimensional stability of the sulfonated polyether ether ketone proton exchange membrane is significantly improved, the swelling rate is reduced, and its application potential in CO2 reduction and hydrogen energy conversion technology is enhanced.
Smart Images

Figure CN119735843A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of proton exchange membrane preparation, in particular to a method for preparing a sulfonated polyetheretherketone proton exchange membrane. Background Art
[0002] At present, the global consumption of fossil energy is huge, the energy crisis and environmental problems are becoming increasingly serious, and the reduction of carbon dioxide and the development and application of renewable clean low-carbon energy are imminent. 2 In reduction, water electrolysis to produce hydrogen, fuel cells and other devices, the proton exchange membrane has the function of selectively transmitting protons and separating electrodes. It is the core component of the above-mentioned industrial technologies, and its performance determines the efficiency of energy conversion.
[0003] Proton exchange membranes are mainly divided into three categories: fully fluorinated, partially fluorinated, and non-fluorinated. They all have a common problem, namely, poor dimensional stability. Taking the sulfonated polyetheretherketone proton exchange membrane in the non-fluorinated membrane as an example, as the number of water molecules increases, the proton exchange membrane will swell, resulting in an increase in the channel size, which in turn causes other molecules (such as oxygen molecules) to pass through, thereby reducing the performance of the proton exchange membrane. If the number of water molecules continues to increase, the proton exchange membrane may eventually decompose and lose its function of preventing gas cross-permeation. In CO 2 Reduction, water electrolysis hydrogen production, fuel cells and other devices, the energy conversion efficiency is reduced by an order of magnitude. At present, researchers have constructed continuous proton transport channels in sulfonated polyetheretherketone through porous titanium dioxide nanotubes. Although the proton conductivity is increased, the swelling rate is higher than that of pure sulfonated polyetheretherketone proton exchange membrane; researchers have used bifunctional NH 2 -UiO-66-SO 3 Although the proton conductivity increases when H is mixed with sulfonated polyetheretherketone, the swelling rate of the composite proton exchange membrane is only 5% lower than that of pure sulfonated polyetheretherketone, reaching 27%, which limits the application of sulfonated polyetheretherketone proton exchange membrane.
[0004] Metal-organic framework materials are a new type of porous organic-inorganic hybrid materials assembled by metal ions and organic ligands. They arrange structural units in a highly ordered manner at the atomic scale. They have the advantages of pre-designed structure, easy functionalization, orderly distribution and adjustable spacing, regular and orderly pores and adjustable size, and high stability. They provide an ideal platform for solving the problem of excessive increase in channel size. Metal-organic framework arrays are micron-scale ordered structures constructed by metal-organic framework materials. They not only have abundant micron-scale pores, but also have good rigidity and are not easy to deform. Therefore, metal-organic framework arrays can be used as skeletons to be compounded in sulfonated polyetheretherketone proton exchange membranes. Sulfonated polyetheretherketone is filled in the pores of metal-organic framework arrays to form channels for proton transmission; the rigid structure of metal-organic framework arrays can also limit the excessive water absorption of sulfonated polyetheretherketone and maintain a low swelling rate. Summary of the invention
[0005] The present invention provides a method for preparing a metal organic framework array modified sulfonated polyetheretherketone proton exchange membrane, wherein the metal organic framework array and the sulfonated polyetheretherketone proton exchange membrane are composited by a spin coating method to obtain the metal organic framework array modified sulfonated polyetheretherketone proton exchange membrane. The preparation method of the present invention realizes the sealing of the sulfonated polyetheretherketone inside the metal organic framework array by composited with the pore structure with good rigidity in the metal organic framework array, and improves its dimensional stability by micro-region confinement. The preparation method is simple to operate, low in energy consumption, and pollution-free, and the prepared metal organic framework array modified sulfonated polyetheretherketone proton exchange membrane can improve its dimensional stability while maintaining the proton conductivity, and has good practicality.
[0006] To achieve the above object, the present invention provides a method for preparing a sulfonated polyetheretherketone proton exchange membrane, comprising the following steps:
[0007] Drying the polyetheretherketone particles, and adding the dried polyetheretherketone into concentrated sulfuric acid to react to obtain a reaction product;
[0008] The reaction product is poured into deionized water and stirred to obtain a light pink filament, and the light pink filament is washed with deionized water and dried to obtain sulfonated polyetheretherketone;
[0009] Pour the ethanolamine aqueous solution into the copper nitrate aqueous solution, stir and then leave to obtain a copper hydroxide nanowire solution;
[0010] The obtained copper hydroxide nanowire solution is filtered to obtain a copper hydroxide nanowire film, which is then transferred to a glass surface;
[0011] The copper hydroxide nanowire film on the glass surface is immersed in a medium-tetrakis (4-carboxyphenyl) porphine solution for reaction, washed with ethanol, and dried to obtain a CuTCPP array;
[0012] The sulfonated polyetheretherketone is added into NN-dimethylformamide, and the sulfonated polyetheretherketone casting solution is obtained after standing.
[0013] The sulfonated polyetheretherketone casting film liquid is dropped on the surface of the CuTCPP array, and the composite is carried out by spin coating. The bubbles are removed by vacuuming. After the solvent evaporates, the sulfonated polyetheretherketone proton exchange membrane modified by the CuTCPP array is obtained.
[0014] Among them, in “pouring the reaction product into deionized water and stirring to obtain a light pink filament, washing the light pink filament with deionized water, and drying to obtain sulfonated polyetheretherketone”, the method also includes:
[0015] The sulfonation degree of the sulfonated polyetheretherketone is 75-85%.
[0016] Among them, in “pouring the ethanolamine aqueous solution into the copper nitrate aqueous solution, stirring and then standing to obtain a copper hydroxide nanowire solution”, the method also includes:
[0017] The concentration of the ethanolamine aqueous solution is 1-2 mmol / L; the concentration of the copper nitrate aqueous solution is 3-5 mmol / L; and the volume ratio of the ethanolamine aqueous solution to the copper nitrate aqueous solution is 1:1.
[0018] Among them, in “dropping sulfonated polyetheretherketone casting film on the surface of CuTCPP array, compounding by spin coating, removing bubbles by vacuuming, and obtaining CuTCPP array-modified sulfonated polyetheretherketone proton exchange membrane after the solvent evaporates”, the method also includes:
[0019] The spin coating conditions are: firstly spin coating at a low speed of 350 to 750 rpm for 10 to 60 s, and then spin coating at a high speed of 2000 to 5000 rpm for 10 to 60 s.
[0020] Among them, in “dropping sulfonated polyetheretherketone casting film on the surface of CuTCPP array, compounding by spin coating, removing bubbles by vacuuming, and obtaining CuTCPP array-modified sulfonated polyetheretherketone proton exchange membrane after the solvent evaporates”, the method also includes:
[0021] The mass ratio of the CuTCPP array to the sulfonated polyetheretherketone is 1 to 5:30.
[0022] Among them, in “immersing the copper hydroxide nanowire film on the glass surface in a medium-tetrakis (4-carboxyphenyl) porphine solution for reaction, washing with ethanol, and drying to obtain a CuTCPP array”, the method also includes:
[0023] The solvent of the meso-tetrakis(4-carboxyphenyl)porphine solution is a mixture of ethanol and N,N-dimethylformamide, and the volume ratio thereof is 1:3.
[0024] The prepared CuTCPP array-modified sulfonated polyetheretherketone proton exchange membrane has a proton conductivity of 0.50 mS / cm to 11.83 mS / cm under the conditions of 65° C. and 95% relative humidity.
[0025] The prepared CuTCPP array-modified sulfonated polyetheretherketone proton exchange membrane has a water absorption rate of 20.1-73.9% and a swelling rate of no more than 5% under the conditions of 65°C and 95% relative humidity.
[0026] The present invention discloses a method for preparing a sulfonated polyetheretherketone proton exchange membrane. The method comprises the following steps: dropping a sulfonated polyetheretherketone casting liquid onto a CuTCPP array, performing compounding by spin coating, removing bubbles by vacuuming, and then introducing the sulfonated polyetheretherketone casting liquid into the CuTCPP array, thereby blocking the sulfonated polyetheretherketone inside the CuTCPP array and improving its dimensional stability by micro-region confinement. The method of the present invention is simple to operate, has low energy consumption, is pollution-free, and is rapid and efficient. The prepared CuTCPP array-modified sulfonated polyetheretherketone proton exchange membrane is subjected to CO 2 It shows great application potential in reduction and hydrogen energy conversion technology, including but not limited to aqueous electrolyte hydrogen, fuel cell original and other technical fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.
[0028] Figure 1 This is a SEM photograph of the surface of the membrane prepared in Example 1.
[0029] Figure 2 This is the XRD pattern of the film prepared in Example 1.
[0030] Figure 3 This is the impedance diagram of the film prepared in Example 1.
[0031] Figure 4 This is a SEM photograph of the surface of the membrane prepared in Example 2.
[0032] Figure 5 This is the XRD pattern of the film prepared in Example 2.
[0033] Figure 6 This is the impedance diagram of the film prepared in Example 2.
[0034] Figure 7 This is a SEM photograph of the surface of the membrane prepared in Example 3.
[0035] Figure 8 This is the XRD pattern of the film prepared in Example 3.
[0036] Fig. 9 This is the impedance diagram of the film prepared in Example 3.
[0037] Fig.10 This is the SEM image of the surface of the metal organic framework in comparison column 1.
[0038] Fig.11 The XRD pattern of the metal organic framework in comparison column 1.
[0039] Fig.12The impedance diagram of the metal organic framework in comparison column 1.
[0040] Fig.13 This is a SEM image of the surface of the membrane prepared in Comparative Column 2.
[0041] Fig.14 The XRD pattern of the film prepared in comparison column 2 is shown.
[0042] Fig.15 The impedance diagram of the film prepared in comparison column 2 is shown.
[0043] Fig.16 The present invention is a flow chart of the method for preparing the sulfonated polyetheretherketone proton exchange membrane. DETAILED DESCRIPTION
[0044] Embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0045] First embodiment:
[0046] Commercially available polyetheretherketone particles were dried at 120°C for 24 hours to remove moisture, 7.5 g of the dried polyetheretherketone was added to 75 ml of concentrated sulfuric acid, reacted in a constant temperature water bath, and mechanically stirred at 50°C for 16 hours. The reaction product was slowly poured into stirred deionized water to obtain light pink filaments; the light pink filaments were washed with a large amount of deionized water to pH = 7.0; and sulfonated polyetheretherketone was obtained after drying for 24 hours.
[0047] The metal organic framework array is a complex of copper ions and meso-tetrakis(4-carboxyphenyl)porphine, which is denoted as CuTCPP array.
[0048] The ethanolamine aqueous solution was quickly poured into the copper nitrate aqueous solution, stirred for 1 minute, and placed at room temperature for 1 day to obtain a copper hydroxide nanowire solution, wherein the concentration of the ethanolamine aqueous solution was 1.6 mM; the concentration of the copper nitrate aqueous solution was 4 mM; and the volume ratio of the ethanolamine aqueous solution to the copper nitrate aqueous solution was 1:1.
[0049] 30 ml of the solution was filtered through a 2 cm diameter microporous filter membrane (pore size 200 nm) to obtain a copper hydroxide nanowire film, which was then transferred to a 6.25 cm 2 The glass surface was placed for 2 hours; the copper hydroxide nanowire film on the glass surface was immersed in a 0.5 mM meso-tetrakis(4-carboxyphenyl)porphine solution, reacted at 65°C for 24 hours, washed with ethanol, and dried to obtain a CuTCPP array. The solvent of the meso-tetrakis(4-carboxyphenyl)porphine solution is a mixture of ethanol and N,N-dimethylformamide, with a volume ratio of 1:3.
[0050] The prepared 0.10g sulfonated polyetheretherketone is added to 1ml NN-dimethylformamide and allowed to stand for 24 hours to obtain a sulfonated polyetheretherketone casting liquid; the prepared sulfonated polyetheretherketone casting liquid is dropped on the surface of the prepared CuTCPP array and composited by spin coating, wherein the rotation speed and time of the spin coating method are first rotated at a low speed of 400 rpm for 20 seconds, then rotated at a high speed of 2000 rpm for 20 seconds, placed in a vacuum drying oven for 24 hours, and then placed in a 50°C oven for 3 hours; after the solvent evaporates, it is peeled off the glass to obtain a CuTCPP array-modified sulfonated polyetheretherketone proton exchange membrane.
[0051] After testing, the CuTCPP array modified sulfonated polyetheretherketone proton exchange membrane prepared in Example 1 has a proton conductivity of 0.30 mS / cm at 65°C and 95% relative humidity; and its swelling rate at 65°C is 0 and its water absorption rate is 31%.
[0052] Second embodiment:
[0053] Commercially available polyetheretherketone particles were dried at 120°C for 24 hours to remove moisture, 7.5 g of the dried polyetheretherketone was added to 75 ml of concentrated sulfuric acid, reacted in a constant temperature water bath, and mechanically stirred at 50°C for 16 hours. The reaction product was slowly poured into stirred deionized water to obtain light pink filaments; the light pink filaments were washed with a large amount of deionized water to pH = 7.0; and sulfonated polyetheretherketone was obtained after drying for 24 hours.
[0054] The metal organic framework array is a complex of copper ions and meso-tetrakis(4-carboxyphenyl)porphine, which is denoted as CuTCPP array.
[0055] The ethanolamine aqueous solution was quickly poured into the copper nitrate aqueous solution, stirred for 1 minute, and placed at room temperature for 1 day to obtain a copper hydroxide nanowire solution, wherein the concentration of the ethanolamine aqueous solution was 1.6 mM; the concentration of the copper nitrate aqueous solution was 4 mM; and the volume ratio of the ethanolamine aqueous solution to the copper nitrate aqueous solution was 1:1.
[0056] 30 ml of the solution was filtered through a 2 cm diameter microporous filter membrane (pore size 200 nm) to obtain a copper hydroxide nanowire film, which was then transferred to a 6.25 cm 2 The glass surface was placed for 2 hours; the copper hydroxide nanowire film on the glass surface was immersed in a 0.5 mM meso-tetrakis(4-carboxyphenyl)porphine solution, reacted at 65°C for 24 hours, washed with ethanol, and dried to obtain a CuTCPP array. The solvent of the meso-tetrakis(4-carboxyphenyl)porphine solution is a mixture of ethanol and N,N-dimethylformamide, with a volume ratio of 1:3.
[0057] The prepared 0.15g sulfonated polyetheretherketone is added to 1ml NN-dimethylformamide and allowed to stand for 24 hours to obtain a sulfonated polyetheretherketone casting liquid; the prepared sulfonated polyetheretherketone casting liquid is dropped on the surface of the prepared CuTCPP array and composited by spin coating, wherein the rotation speed and time of the spin coating method are first rotated at a low speed of 500 rpm for 30 seconds, then rotated at a high speed of 3000 rpm for 30 seconds, placed in a vacuum drying oven for 24 hours, and then placed in a 50°C oven for 3 hours; after the solvent evaporates, it is peeled off the glass to obtain a CuTCPP array-modified sulfonated polyetheretherketone proton exchange membrane.
[0058] After testing, the CuTCPP array modified sulfonated polyetheretherketone proton exchange membrane prepared in Example 2 has a proton conductivity of 0.92 mS / cm at 65°C and 95% relative humidity; and its swelling rate at 65°C is 0 and its water absorption rate is 57%.
[0059] Third embodiment:
[0060] Commercially available polyetheretherketone particles were dried at 120°C for 24 hours to remove moisture, 7.5 g of the dried polyetheretherketone was added to 75 ml of concentrated sulfuric acid, reacted in a constant temperature water bath, and mechanically stirred at 50°C for 16 hours. The reaction product was slowly poured into stirred deionized water to obtain light pink filaments; the light pink filaments were washed with a large amount of deionized water to pH = 7.0; and sulfonated polyetheretherketone was obtained after drying for 24 hours.
[0061] The metal organic framework array is a complex of copper ions and meso-tetrakis(4-carboxyphenyl)porphine, which is denoted as CuTCPP array.
[0062] The ethanolamine aqueous solution was quickly poured into the copper nitrate aqueous solution, stirred for 1 minute, and placed at room temperature for 1 day to obtain a copper hydroxide nanowire solution, wherein the concentration of the ethanolamine aqueous solution was 1.6 mM; the concentration of the copper nitrate aqueous solution was 4 mM; and the volume ratio of the ethanolamine aqueous solution to the copper nitrate aqueous solution was 1:1.
[0063] 30 ml of the solution was filtered on a 2 cm diameter microporous filter membrane (pore size 200 nm) to obtain a copper hydroxide nanowire film, which was then transferred to a 6.25 cm2 glass surface and left for 2 hours; the copper hydroxide nanowire film on the glass surface was immersed in a 0.5 mM meso-tetrakis(4-carboxyphenyl)porphine solution, reacted at 65°C for 24 hours, washed with ethanol, and dried to obtain a CuTCPP array. The solvent of the meso-tetrakis(4-carboxyphenyl)porphine solution is a mixture of ethanol and N,N-dimethylformamide, with a volume ratio of 1:3.
[0064] The prepared 0.20g sulfonated polyetheretherketone is added to 1ml NN-dimethylformamide and allowed to stand for 24 hours to obtain a sulfonated polyetheretherketone casting liquid; the prepared sulfonated polyetheretherketone casting liquid is dropped on the surface of the prepared CuTCPP array and composited by spin coating, wherein the rotation speed and time of the spin coating method are first rotated at a low speed of 600 rpm for 40 seconds, then rotated at a high speed of 4000 rpm for 40 seconds, placed in a vacuum drying oven for 24 hours, and then placed in a 50°C oven for 3 hours; after the solvent evaporates, it is peeled off the glass to obtain a CuTCPP array-modified sulfonated polyetheretherketone proton exchange membrane.
[0065] After testing, the CuTCPP array modified sulfonated polyetheretherketone proton exchange membrane prepared in Example 3 has a proton conductivity of 15.90 mS / cm at 65°C and 95% relative humidity; and its swelling rate at 65°C is 0 and its water absorption rate is 77%.
[0066] Comparative column 1: Preparation of metal organic framework arrays:
[0067] The metal organic framework array is a complex of copper ions and meso-tetrakis(4-carboxyphenyl)porphine, which is denoted as CuTCPP array.
[0068] The ethanolamine aqueous solution was quickly poured into the copper nitrate aqueous solution, stirred for 1 minute, and placed at room temperature for 1 day to obtain a copper hydroxide nanowire solution, wherein the concentration of the ethanolamine aqueous solution was 1.6 mM; the concentration of the copper nitrate aqueous solution was 4 mM; and the volume ratio of the ethanolamine aqueous solution to the copper nitrate aqueous solution was 1:1.
[0069] 30 ml of the solution was filtered through a 2 cm diameter microporous filter membrane (pore size 200 nm) to obtain a copper hydroxide nanowire film, which was then transferred to a 6.25 cm 2 The glass surface was placed for 2 hours; the copper hydroxide nanowire film on the glass surface was immersed in a 0.5 mM meso-tetrakis(4-carboxyphenyl)porphine solution, reacted at 65°C for 24 hours, washed with ethanol, and dried to obtain a CuTCPP array. The solvent of the meso-tetrakis(4-carboxyphenyl)porphine solution is a mixture of ethanol and N,N-dimethylformamide, with a volume ratio of 1:3.
[0070] According to the test, the proton conductivity of the organic metal framework array prepared in comparison column 1 is only 0.001 mS / cm under the conditions of 65° C. and 95% relative humidity.
[0071] Comparative column 2: Preparation of pure sulfonated polyetheretherketone:
[0072] Commercially available polyetheretherketone particles were dried at 120°C for 24 hours to remove moisture, 7.5 g of the dried polyetheretherketone was added to 75 ml of concentrated sulfuric acid, reacted in a constant temperature water bath, and mechanically stirred at 50°C for 16 hours. The reaction product was slowly poured into stirred deionized water to obtain light pink filaments; the light pink filaments were washed with a large amount of deionized water to pH = 7.0; and sulfonated polyetheretherketone was obtained after drying for 24 hours.
[0073] 0.20 g of the prepared sulfonated polyetheretherketone was added to 1 ml of NN-dimethylformamide and allowed to stand for 24 hours to obtain a sulfonated polyetheretherketone casting solution; the prepared sulfonated polyetheretherketone casting solution was dropped on a 6.25 cm 2 The glass surface is evenly coated by spin coating, wherein the rotation speed and time of the spin coating method are: first rotate at a low speed of 600 rpm for 40 seconds, then rotate at a high speed of 4000 rpm for 40 seconds, and place it in a 50°C oven for 3 hours; after the solvent evaporates, it is peeled off the glass to obtain a pure sulfonated polyetheretherketone proton exchange membrane.
[0074] After testing, the pure sulfonated polyetheretherketone proton exchange membrane prepared in comparison column 2 has a proton conductivity of 37.56 mS / cm at 65°C and 95% relative humidity; its swelling rate at 65°C is 56% and its water absorption rate is 87%.
[0075] What is disclosed above is only one or more preferred embodiments of the present application, and cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiments and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.
Claims
1. A method for preparing a sulfonated polyetheretherketone proton exchange membrane, characterized in that it comprises the following steps: Drying the polyetheretherketone particles, and adding the dried polyetheretherketone into concentrated sulfuric acid to react to obtain a reaction product; The reaction product is poured into deionized water and stirred to obtain a light pink filament, and the light pink filament is washed with deionized water and dried to obtain sulfonated polyetheretherketone; Pour the ethanolamine aqueous solution into the copper nitrate aqueous solution, stir and then leave to obtain a copper hydroxide nanowire solution; The obtained copper hydroxide nanowire solution is filtered to obtain a copper hydroxide nanowire film, which is then transferred to a glass surface; The copper hydroxide nanowire film on the glass surface is immersed in a medium-tetrakis (4-carboxyphenyl) porphine solution for reaction, washed with ethanol, and dried to obtain a CuTCPP array; The sulfonated polyetheretherketone is added into NN-dimethylformamide, and the sulfonated polyetheretherketone casting solution is obtained after standing. The sulfonated polyetheretherketone casting film liquid is dropped on the surface of the CuTCPP array, and the composite is carried out by spin coating. The bubbles are removed by vacuuming. After the solvent evaporates, the sulfonated polyetheretherketone proton exchange membrane modified by the CuTCPP array is obtained.
2. The method for preparing a sulfonated polyetheretherketone proton exchange membrane according to claim 1, characterized in that: In "pouring the reaction product into deionized water and stirring to obtain a light pink filament, washing the light pink filament with deionized water, and drying to obtain sulfonated polyetheretherketone", the method further comprises: The sulfonation degree of the sulfonated polyetheretherketone is 75-85%.
3. The method for preparing a sulfonated polyetheretherketone proton exchange membrane according to claim 1, characterized in that: In “pouring the ethanolamine aqueous solution into the copper nitrate aqueous solution, stirring and then standing to obtain a copper hydroxide nanowire solution”, the method further includes: The concentration of the ethanolamine aqueous solution is 1-2 mmol / L; the concentration of the copper nitrate aqueous solution is 3-5 mmol / L; and the volume ratio of the ethanolamine aqueous solution to the copper nitrate aqueous solution is 1:
1.
4. The method for preparing a sulfonated polyetheretherketone proton exchange membrane according to claim 1, characterized in that: In "dropping sulfonated polyetheretherketone casting film on the surface of CuTCPP array, compounding by spin coating, removing bubbles by vacuuming, and obtaining CuTCPP array-modified sulfonated polyetheretherketone proton exchange membrane after the solvent evaporates", the method also includes: The spin coating conditions are: firstly spin coating at a low speed of 350 to 750 rpm for 10 to 60 s, and then spin coating at a high speed of 2000 to 5000 rpm for 10 to 60 s.
5. The method for preparing a sulfonated polyetheretherketone proton exchange membrane according to claim 1, characterized in that: In "dropping sulfonated polyetheretherketone casting film on the surface of CuTCPP array, compounding by spin coating, removing bubbles by vacuuming, and obtaining CuTCPP array-modified sulfonated polyetheretherketone proton exchange membrane after the solvent evaporates", the method also includes: The mass ratio of the CuTCPP array to the sulfonated polyetheretherketone is 1 to 5:
30.
6. The method for preparing a sulfonated polyetheretherketone proton exchange membrane according to claim 1, characterized in that: In "immersing the copper hydroxide nanowire film on the glass surface in a solution of meso-tetrakis(4-carboxyphenyl)porphine for reaction, washing with ethanol, and drying to obtain a CuTCPP array", the method further includes: The solvent of the meso-tetrakis(4-carboxyphenyl)porphine solution is a mixture of ethanol and N,N-dimethylformamide, and the volume ratio thereof is 1:
3.
7. The method for preparing a sulfonated polyetheretherketone proton exchange membrane according to claim 1, characterized in that: The prepared CuTCPP array-modified sulfonated polyetheretherketone proton exchange membrane has a proton conductivity of 0.50 mS / cm to 11.83 mS / cm under the conditions of 65° C. and 95% relative humidity.
8. The method for preparing a sulfonated polyetheretherketone proton exchange membrane according to claim 1, characterized in that: The prepared CuTCPP array-modified sulfonated polyetheretherketone proton exchange membrane has a water absorption rate of 20.1-73.9% and a swelling rate of no more than 5% under the conditions of 65°C and 95% relative humidity.